2017
DOI: 10.1007/s00702-017-1818-4
|View full text |Cite
|
Sign up to set email alerts
|

Premonitory Urge for Tics Scale (PUTS): replication and extension of psychometric properties in youth with chronic tic disorders (CTDs)

Abstract: Individuals with chronic tic disorders (CTDs) frequently describe aversive subjective sensory sensations that precede their tics. The first aim of the present study was to explore the psychometric properties of a standardized self-report measure to assess premonitory urges in CTDs, The Premonitory Urge for Tics Scale (PUTS), by replicating the analyses of Woods et al. (J Dev Behav Pediatr 26:397-403, 2005) using a sample twice the size of theirs. The second aim was to conduct an exploratory factor analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
46
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(58 citation statements)
references
References 24 publications
10
46
2
Order By: Relevance
“…The aim of the present study, therefore, was to examine the psychometric properties of the PUTS in a large sample of 656 children, aged 3-16 years (of which 356 children were below 11 years) from an European multicenter study. We aimed to replicate previous work [12,16,17] and to further investigate the psychometric properties in young children. First, we investigated the internal consistency of the PUTS.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 95%
See 4 more Smart Citations
“…The aim of the present study, therefore, was to examine the psychometric properties of the PUTS in a large sample of 656 children, aged 3-16 years (of which 356 children were below 11 years) from an European multicenter study. We aimed to replicate previous work [12,16,17] and to further investigate the psychometric properties in young children. First, we investigated the internal consistency of the PUTS.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 95%
“…The Premonitory Urge for Tics Scale (PUTS [12]) is the most frequently used self-report measure to assess the severity of premonitory urges. Studies investigating the psychometric properties of the PUTS have so far indicated a good internal reliability and correlations with the Yale Global Tic Severity Scale (YGTSS [15]) for children of 11 years and older, but not for younger children [12,16,17]. Similarly, PUTS scores of children aged 11 years and older (and not younger children) correlated well with the Children's Yale-Brown Obsessive Compulsive Scale (CY-BOCS [18]), which might not be surprising given that some premonitory urges (i.e.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
See 3 more Smart Citations